1992
DOI: 10.1557/jmr.1992.0605
|View full text |Cite
|
Sign up to set email alerts
|

The effect of strain rate and temperature on the tensile properties of NiAl

Abstract: Tensile testing of cast and extruded binary NiAl was performed from 300 to 900 K at strain rates of 1.4 × 10−4 to 1.4 × 10−1 × s−1. The brittle-to-ductile transition temperature (BDTT) was dependent on strain rate, with a three order of magnitude increase in strain rate resulting in approximately a 200 K increase in transition temperature. Regardless of strain rate, at temperatures just above the BDTT the fracture strength increased significantly and the fracture morphology changed from mostly intergranular to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(30 citation statements)
references
References 20 publications
3
24
0
Order By: Relevance
“…This description is consistent with in-situ transmission electron microscope annealing studies on NiAl that have qualitatively determined the temperatures for which dislocation climb by short circuit and bulk diffusion processes becomes significant . This description of the deformation behavior of polycrystalline NiAl near the brittle-to-ductile transition is also consistent with the observed effects of strain rate and alloying additions on the BDTT (Noebe, Cullers, and Bowman 1992;Noebe 1994). Dislocation climb processes driven by short circuit diffusion along dislocation cores could similarly be used to explain the brittle-to-ductile transition in [001 ]-oriented single crystals.…”
Section: Ductility and Fracturesupporting
confidence: 84%
See 2 more Smart Citations
“…This description is consistent with in-situ transmission electron microscope annealing studies on NiAl that have qualitatively determined the temperatures for which dislocation climb by short circuit and bulk diffusion processes becomes significant . This description of the deformation behavior of polycrystalline NiAl near the brittle-to-ductile transition is also consistent with the observed effects of strain rate and alloying additions on the BDTT (Noebe, Cullers, and Bowman 1992;Noebe 1994). Dislocation climb processes driven by short circuit diffusion along dislocation cores could similarly be used to explain the brittle-to-ductile transition in [001 ]-oriented single crystals.…”
Section: Ductility and Fracturesupporting
confidence: 84%
“…However, the BDTT for polycrystalline NiAI is strongly affected by strain rate. A 3 orders of magnitude increase in strain rate results in approximately a 200 K increase in BDTT (Noebe, Cullers, and Bowman 1992). A similar rate dependence of the BDTT is observed in 10011 single crystals .…”
Section: Yield Strengthsupporting
confidence: 72%
See 1 more Smart Citation
“…Some studies reported that the improvement of the NiAl alloy's room temperature ductility are governed by the presence of β-phase (Ni,Cu)Al and γ'-phase (Ni,Cu) 3 Al [19,20]. Furthermore, there are many studies in the literature that have reported the quasi-static loading condition (under low strain rate) performance of NiAl intermetallic alloy [21][22][23]. However, previous studies have not investigated the effect of the high strain rate on the mechanical and fracture properties of NiAl intermetallic alloy.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] These materials have interesting potential in ignition, combustion synthesis, and nano-scale heating applications. [3] However, RNLs have been most popularly used as localized heat sources in joining technologies, such as brazing or soldering. [4][5][6] The self-propagating nature of the exothermic reaction occurring between the layers, typically Ni and Al, provides a promising and functional heat source.…”
mentioning
confidence: 99%